Circular Economy and Resource Efficiency in Industrial Competitiveness - Marieska Lupikawaty (PT. Anagata Sembagi Education, 2025)
The transition toward a low-carbon economy has pushed industries to adopt circular economy and resource efficiency not merely as environmental initiatives, but as strategic drivers of competitiveness. However, academic studies examining the relationship between circular economy, resource efficiency, and industrial competitiveness remain fragmented and report inconsistent findings. This study aims to systematically analyze the contribution of circular economy and resource efficiency to industrial competitiveness and to identify the key mechanisms underlying this relationship. A systematic literature review was conducted using an evidence-based industrial sustainability approach, synthesizing peer-reviewed journal articles published between 2020 and 2025 and selected through the PRISMA process. The findings indicate that circular economy enhances industrial competitiveness primarily through improvements in resource efficiency, leading to cost reduction, supply stability, productivity gains, and process innovation. Resource efficiency emerges as a critical mediating mechanism translating circular practices into measurable competitive advantages. Nevertheless, the strength of evidence varies across industrial sectors, firm sizes, and institutional contexts. This study concludes that circular economy and resource efficiency act as strategic enablers of industrial competitiveness when implemented systematically and contextually, rather than as universally applicable solutions.